Determination of the physicochemical properties and 13 C/ 12 C isotope ratios of some honeys from the northeast Anatolia region of Turkey - Cengiz, Mahir Murat; Tosun, Murat; Topal, Mehmet (Elsevier BV, 2018)
Abstract In the study, the honey was subjected to analyses after being taken from different producers immediately after the end of the production season. 13C/12C analysis was performed on the samples using an isotope ratio mass spectrometer (EA-IRMS) combined with an elemental analyzer. In all of the honey samples, the δ13C value was found to be more negative than −23.5‰ and even the C4 sugar ratio was found to be lower than 7%. The results from the physicochemical analysis of the samples were determined to be 15.9 ± 1.6% for the moisture content, 82.8 ± 1.1 for brix, 0.183 ± 0.02 mS/cm for conductivity, 24.4 ± 4.0 meq/kg for total acidity, 546 ± 80 mg/kg for proline, and 14.5 ± 3.5 for diastase activity. In addition, the sugar content was determined to be 38.8 ± 1.8% for fructose, 30.2 ± 1.7% for glucose, 69.1 ± 3.3% for fructose + glucose, and 1.29 ± 0.5 for fructose/glucose. When the analysis results were evaluated according to the relevant standards and codex, it was evident that the honey samples produced within the region are of very good quality.
Keywords: 6. Clean water